2019
DOI: 10.1038/s41467-019-12428-7
|View full text |Cite
|
Sign up to set email alerts
|

ABCC9-related Intellectual disability Myopathy Syndrome is a KATP channelopathy with loss-of-function mutations in ABCC9

Abstract: Mutations in genes encoding KATP channel subunits have been reported for pancreatic disorders and Cantú syndrome. Here, we report a syndrome in six patients from two families with a consistent phenotype of mild intellectual disability, similar facies, myopathy, and cerebral white matter hyperintensities, with cardiac systolic dysfunction present in the two oldest patients. Patients are homozygous for a splice-site mutation in ABCC9 (c.1320 + 1 G > A), which encodes the sulfonylurea receptor 2 (SUR2) subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…Interestingly, there does not appear to be any obvious skeletal muscle defect, although Albaqumi et al (2014) described a family with congenital hyperinsulinism and rhabdomyolysis associated with Kir6.2 mutations (Albaqumi et al, 2014), and Flanagan et al (2017) recently reported a patient with persistent hyperinsulinaemic hypoglycaemia and severe hypotonia resulting from an activating mutation in a calcium channel subunit, which etiologically may have the same basis (Flanagan et al, 2017). Recently, we described a novel ABCC9-related Intellectual disability Myopathy Syndrome (AIMS) resulting from loss-offunction mutations in ABCC9 (SUR2) (Smeland et al, 2019), in which patients also exhibit muscular pain and fatigue, and evidence of muscle fiber damage.…”
Section: Discussion Katp Channels and Skeletal Musclementioning
confidence: 99%
“…Interestingly, there does not appear to be any obvious skeletal muscle defect, although Albaqumi et al (2014) described a family with congenital hyperinsulinism and rhabdomyolysis associated with Kir6.2 mutations (Albaqumi et al, 2014), and Flanagan et al (2017) recently reported a patient with persistent hyperinsulinaemic hypoglycaemia and severe hypotonia resulting from an activating mutation in a calcium channel subunit, which etiologically may have the same basis (Flanagan et al, 2017). Recently, we described a novel ABCC9-related Intellectual disability Myopathy Syndrome (AIMS) resulting from loss-offunction mutations in ABCC9 (SUR2) (Smeland et al, 2019), in which patients also exhibit muscular pain and fatigue, and evidence of muscle fiber damage.…”
Section: Discussion Katp Channels and Skeletal Musclementioning
confidence: 99%
“…Briefly, an indel mutation in ABCC9 (c.3446_3450delACTTCinsGA) resulting in introduction of a premature stop codon (p.Y1148Stop) was generated using CRISPR/Cas9‐mediated genome engineering (Smeland et al . 2019). Heterozygous SUR2 wt/Stop mice were intercrossed to generate homozygous SUR2 Stop/Stop (referred to as SUR2[STOP]) and wild‐type littermates, which were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the finding that R1154Q induces such splicing in any genome illustrates the principle that SUR2 GOF mutations can also be associated with additional LOF resulting from variable splicing that leads to reduced protein levels, such that the net effect could be either GOF or LOF in different tissues. We have demonstrated that isolated SUR2 LOF results in a very distinct constellation of features in ABCC9-related intellectual myopathy syndrome (AIMS) ( 49 ). Hence, dual GOF/LOF consequences of CS mutations could result in not just quantitatively, but qualitatively variable outcomes and marked variability of CS pathologies, and hence might underlie the marked variation in severity of CS consequences that is seen in patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%